Productivity and Efficiency Improvement Using Witness Simulation and Ergonomic Study in Automotive Assembly Line - Ahmad Shah Hizam, Md. Yasir; N. M. Zuki, N. M. (Universidade NOVA de Lisboa, Portugal, 2017)
The most crucial part of manufacturing industry is the assembly line because it will determine the efficiency and the productivity of the companies. There are many aspects of improvement that can be executed to achieve optimum efficiency and productivity of production system. This paper is focusing on the 2 factor of improving the automotive assembly line. First objective is to study the ergonomic level and second objective is to improve the assembly line balancing. An ergonomic system in automotive assembly line plays a vital role to lower the risk of injury of musculoskeletal disorder (MSD) among employees. The assembly line can be improved such in many ways, for example, the arrangement of working layout, the height of the workplace and how the worker is handling the piece part. All of these are imperative to increase the efficiency of employees. The research was conducted at an ABC automotive company in Pahang, Malaysia. The existing productivity and efficiency of assembly line was studied. The study involves a total of four main stations on the assembly line. The increment percentage of labor and station efficiencies is tabulate to show the comparison before and after layout improvement was done